Pelatihan Pola Makan Sehat Keluarga kepada Komunitas Theresia Lisieux, Apartemen Mediterania 1, Jakarta Barat, Kelurahan Tanjung Duren, Kecamatan Grogol Petamburan, Jakarta Barat - Widyastuti, Wiena; O Iskandar, Bernardus; Zen, Yuniar; Sahelangi, Olivia (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2023)
The COVID-19 pandemic poses the challenge ofining a healthy and varied diet and regular physical activity. This is because people prefer to buy processed foods, such as snacks, fast food, and ready-to-eat cereals, which tend to be high in fat, sugar, and salt. In addition, psychological and emotional responses to the outbreak of COVID-19 can increase the risk of developing dysfunctional eating behavior. The choice of foods and how often they are eaten can affect the health of the body, teeth, and gums. Excessive consumption of sugar-containing soda, fruit drinks with added sugar, or low-nutritional snacks can increase the risk of teeth hole. Therefore, a community service program (PkM) was designed with the aim of providing education and training to the community to gain knowledge about diet and improve health. The development and training of a healthy diet to the Lisiuex Apartment Meditarenia 1 West Jakarta community was conducted online, illustrating the improvement of the participants' knowledge and yielding good results. Sustainable education and training programmes are needed as a means of improving the development of health that starts with the family.